عادات تسمية المواليد عند المغول - فرطوس حيدر, عبد الرحمن (Al-Adab Journal, 2018)
This research deals with the traditions of naming the newborns in Mongolian society during thirteenth century, and the main importance of this subject comes from ,that any attempt to understand the meaning of common Mongolian names gives many advantages for the specialist in the field of historical Mongolian studies , because this knowledge provides a deeper understanding about one of the traditions of these tribes who appeared to the world suddenly and horribly, as well as , It gives the knowledge of the type of social consciousness that prevailed among them, and explains the nature behavior towards other people The most important results of this research ; The Mongols Were inherited ancient traditions in the practice of naming their newborns ,as well as the Mongolian names in general can be divided into main categories : names which represent a good and desirable qualities in life, names which represent the numbers, names which represent the special and general events, animal names ,because most of Mongols were practice herding and hunting, names that are derived from beautiful objects and precious things etc.